The fate of Siberian civilization - M. V. Shilovskiy (Омский научный вестник: Серия "Общество. История. Современность")
The publication is a reaction to the articles of P. A. Yeltsov and A. V. Sushko regarding the prospects for the incorporation of Siberia into the all-Russian civilizational space taking into account the positions of Siberian oblasts. The author is skeptical about the prospects for the separation of Asian Russia in the foreseeable future and is trying to argue his point of view